Two-weight norm inequalities for the rough fractional integrals - Yong Ding; Chin-Cheng Lin (International Journal of Mathematics and Mathematical Sciences)
The authors give the weighted (Lp,Lq)-boundedness of the rough fractional integral operator TΩ,α and the fractional maximal operator MΩ,α with two different weight functions.